Weir of Hermiston - Stevenson, Robert Louis, 1850-1894 (New Edinburgh edition of the works of Robert Louis Stevenson., 2017)
Stevensoń⁰₉s unfinished masterpiece, Weir of Hermiston, has been entirely re-edited from his final manuscript, revealing a rather different novel from the bowdlerised version produced posthumously by his friends. Stevenson revisits the conflicted Scotland of James Hogg and Sir Walter Scott as well as that of his own youth, but also responds to recently published novels. A substantial essay explores the complex early publication history of the novel on both sides of the Atlantic, and exceptionally full explanatory notes and other background information are provided.